Agreement of measures between measured body adiposity and calculated indices of fatness in sedentary and active male and female students - Malara Marzena; Kęska Anna; Tkaczyk Joanna; Lutosławska Grażyna (Sciendo, 2022)
Study aim: Our study was undertaken to analyze agreement between measured body fat and different indices of fatness in students of both sexes and with different physical activity.